Study on the Carrier Transport Process in Deep Ultraviolet Light-Emitting Diodes with Al-Content-Varied AlGaN Composite Last Quantum Barrier - Wei Liu; Yujia Liu; Junhua Gao; Zeyu Liu; Bohan Shi; Linyuan Zhang; Xinnan Zhao; Runzhi Wang (Micromachines)
Serious electron leakage and poor hole injection efficiency are still challenges for deep ultraviolet AlGaN-based light-emitting diodes with a traditional structure in achieving high performance. Currently, the majority of research works concentrate on optimizing the structures of the electron blocking layer (EBL) and last quantum barrier (LQB) separately, rather than considering them as an integrated structure. Therefore, in this study, an Al-content-varied AlGaN composite last quantum barrier (CLQB) layer is proposed to replace the traditional EBL and LQB layers. It is found that when the Al content in the CLQB decreases from 70% to 60% along the growth direction, the sample’s luminescence efficiency is improved, which can be ascribed to the higher carrier concentration in the multiple quantum well active region caused by suppressed electron leakage and enhanced hole injection. Additionally, in the CLQB structure, the carrier loss at the EBL/LQB hetero-interface, which is inevitable in the traditional structure, can be avoided. However, if the Al content in the CLQB changes in an opposite way, i.e., increasing from 60% to 70%, the device optoelectronic performance deteriorates, since the electron leakage is enhanced and the hole injection is suppressed.